The Yanus-Like Quality of the Ukrainian Audit - REDKOО. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2020)
The external control over the quality of audit is exercised in Ukraine due to the requirement of the specialized law, in spite of the missing definition of the quality of audit and its criteria in domestic and international normative documents. The article’s objective is to draw attention to the issue of the quality of audit by elaborating on its dual nature, terms and principles for organization of control over business results of auditing entities and user expectations concerning these results. For this purpose, the quality of audit is addressed from two dimensions: external and internal. The external dimension of the quality of audit is analyzed in terms of expectations concerning the quality of audit, held by users of audit results (official regulatory bodies of bank, financial and corporate relations; official fiscal bodies and controlling bodies of public supervision over auditors; actual owners of businesses; hired management) and the coincidence between these expectations and actual results of audit. The internal dimension of the quality of audit is analyzed in terms of auditing entities and their expectations from the categories of entities such as customers, owners of customers, controlling bodies, personnel of auditing entities or invited external auditors or experts. Distinctive features of the Ukrainian market of audit services are highlighted, prevalence of supply over demand in the first place. Questions are posed which need to be responded for proper organization of control over the quality of audit: Is control over the quality of audit is necessary? If “yes”, then to whom? Do formalized expectations of users of audit results concerning the quality of its result really exist? If audit is a type of control over the quality of reporting and management on the whole, would it be expedient to set up control over the controller? What is the essential meaning of effectiveness and performance of control over the quality of audit, especially external one? Can positive results of the external inspection of auditing entities to the effect of the quality of audit be regarded as “indulgence” for a certain period, or the permanent external control is needed after all? Should control over the quality of audit be obligatory only for the auditing entities involved in inspections of entities of public interest, or should it cover all the auditing entities without exception? The analysis gave grounds to the author to ask if it would be more expedient in the Ukrainian realities that the term “quality of auditing” was abandoned and replaced by the term “compliance with the standards”.